1991
DOI: 10.1164/ajrccm/143.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Theophylline on Sleep and Sleep-disordered Breathing in Patients with Chronic Obstructive Pulmonary Disease

Abstract: To investigate the effect of theophylline on sleep and sleep-disordered breathing in patients with chronic obstructive pulmonary disease (COPD), we studied 12 male nonhypercapnic subjects with a mean +/- SEM age of 62.8 +/- 2.5 yr and a FEV1 of 1.36 +/- 0.11 L using a randomized double-blind crossover protocol. Sustained-action theophylline (250 mg three times or four times a day) or placebo was administered for 2 days, and the alternate drug was administered on the following 2 days. Sleep studies were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 5 publications
0
17
0
2
Order By: Relevance
“…Veale and coworkers (38) noted no change in sleep quality in 14 patients with COPD treated with a sustained-release form of salbutamol. The effects of theophylline on sleep quality have been more variable, with some studies demonstrating an impairment in sleep quality (39), whereas others have noted no significant effect (40)(41)(42). Anticholinergics such as ipratropium may improve sleep quality (43).…”
Section: Mechanisms Responsible For Poor Sleep Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Veale and coworkers (38) noted no change in sleep quality in 14 patients with COPD treated with a sustained-release form of salbutamol. The effects of theophylline on sleep quality have been more variable, with some studies demonstrating an impairment in sleep quality (39), whereas others have noted no significant effect (40)(41)(42). Anticholinergics such as ipratropium may improve sleep quality (43).…”
Section: Mechanisms Responsible For Poor Sleep Qualitymentioning
confidence: 99%
“…As noted above, bronchodilator medications have shown mixed results regarding their effects on sleep quality, with some demonstrating improvement (43), no significant effect (40)(41)(42)44), or deterioration in sleep quality (39). However, despite their diverse effects on sleep quality, the majority have demonstrated an improvement in nocturnal oxygen saturation (39,41,43,44) and lung function (39)(40)(41)(42)(43)(44).…”
Section: Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ipratropium bromide enhances sleep quality, abrogates nocturnal oxygen desaturation, improves perceived sleep quality, and increases REM sleep duration without any effects on other sleep phases or total sleep duration [66]. On the other hand, while some studies examining the effect of Theophylline on sleep quality reported that it caused deterioration of sleep quality [65], other studies revealed that it had no effect on sleep quality [67][68][69].…”
Section: Patient B "Sometimes I Have a Stuffed Throat And Become Shomentioning
confidence: 99%
“…6. Theophylline: Berry et al demonstrated improvement in overnight oxygen saturation and transcutaneous CO 2 after oral ingestion of theophylline during non-REM sleep in non-hypercapnic patients with COPD (76) . The effects were not carried on during REM sleep.…”
Section: Bronchodilatorsmentioning
confidence: 99%